Síntese de 4,5-bis(trifluormetil)-1h-pirazóis através de reações eletrofílicas e nucleofílicas empregando NIS e MFSDA - Junges, Andrizia de Freitas (2019)
This dissertation describes the development of an efficient methodology for the functionalization of position 4 of 3-alkyl(aryl)-1-aryl-5-trifluoromethyl-1H-pyrazoles systems by halogenation and subsequent reaction with trifluoromethylating reagent MFSDA, thus obtaining a series of six unpublished examples of 4-iodo-5-trifluoromethyl-1H -pyrazoles in addition to seven unpublished compounds of the 4,5- bis(trifluoromethyl)-1H-pyrazoles series. Initially eight examples of 1-aryl-3-alkyl (aryl) -5-trifluoromethyl-1H-pyrazoles where aryl = C6H5, 4-FC6H4, 4-ClC6H4 and alkyl = Me, c-Pr, i-Pr, n-Bu from the cyclocondensation reaction [3 + 2] between 4-alkyl (aryl) -4-alkoxy-1,1,1-trifluoro-3-alken-2-ones and arylhydrazines in yields of 91-94%. The synthesized starting materials were then subjected to CF3COOH -catalyzed electrophilic iodination using the N-iodosuccinimide (NIS) reagent resulting in a series of 4-iodo-5-trifluoromethyl-1H-pyrazoles in yields of 75-87%. Subsequently the optimization of the methodology of insertion of trifluoromethyl at the 4-position of the series of 4-iodo-5-trifluoromethyl-1H-pyrazoles through nucleophilic substitution using the MFSDA reagent was performed. For this, different copper salts and additives were tested, besides the study of the reaction in argon atmosphere. By optimizing the methodology it was possible to synthesize an unpublished series of 4,5-bis(trifluoromethyl)-1H-pyrazoles in yields of up to 79%.